A Means of Control of The European Hen Flea (Ceratophyllus Gallinae Schrank). Issue 1 (22nd August 2014) - Stewart, M. A.
Abstract : This paper very briefly describes the control of the European hen flea ( Ceratophyllus gallinae Schrank), a potential pest of considerable economic importance to poultrymen, by spraying the buildings with Phinotas Disinfectant and dipping the birds in the same material.